MICHIGAN SENATE BILL 486 'CLEAN INDOOR AIR ACT' - KELLY,J (Tufts Archival Research Center, 2007)
Memo to the State Activities Policy Committee of TAN regarding a bill in Michigan that would restrict smoking in the workplace as well as in public spaces. Asks for approval to mobilize TAN activists against the bill and lists several proposals for ways in which to do so. Attaches a copy of the bill and template for letters to be written to local legislators.